Pelatihan Pembuatan Terrarium untuk Mengembangkan Metakognisi dan Sikap Entrepreneurship Siswa di MA Roudlotul Mubtadiin, Jepara - Azizul Ghofar Candra Wicaksono; Atip Nurwahyunani; Ipah Budi Minarti; Muhammad Amiruddin (Pelita: Jurnal Pengabdian kepada Masyarakat, 2026)
This workshop program aimed to develop students' metacognition and entrepreneurial attitudes through terrarium-making activities integrated into biology learning at MA Roudlotul Mubtadiin, Jepara. The workshop was implemented in several sessions. First, students attended a lecture and discussion on the concepts of terrariums, metacognition, and entrepreneurship. Second, students worked in groups to create their own terrariums. Following the workshop, students' metacognition and entrepreneurial attitudes were assessed using questionnaires. The results showed that more than 60% of the students demonstrated positive entrepreneurial attitudes, reflecting their interest in participating in entrepreneurship learning and related programs. Furthermore, students exhibited high levels of metacognition (M = 75.55–77.72), indicating their ability to plan, monitor, regulate, and evaluate their work effectively. Therefore, the terrarium-making workshop program has the potential to enhance students' metacognition and entrepreneurial attitudes.